2018
DOI: 10.1097/cmr.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Acral melanoma: a retrospective cohort from the Brazilian National Cancer Institute (INCA)

Abstract: Acral melanoma (AM) is a rare subtype of melanoma arising on the palms, soles and subungual areas. In the Brazilian and Latin American populations, the sociodemographic and clinical-pathologic features of AM are unclear. AM tends to be more advanced at presentation because of delayed diagnoses, with poor survival. This study reports on a retrospective AM cohort from the Brazilian National Cancer Institute. We reviewed a database of 529 patients presenting with AM from 1997 to 2014 and analysed the sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
23
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 40 publications
12
23
2
3
Order By: Relevance
“…We have also shown that the most common histological subtype in HFM is ALM, which stays in concordance with studies of other authors such as Durbec et al, Albreski et al,Jung et al,Nunes et al [2,9,28,30]. Many HFMs were ulcerated (62.4%), which is consistent with the retrospective literature in this MM group [2,30,33]. In the HFM group, we found a higher median Breslow thickness (3.3 mm) than reported by Bello (2.1 mm) [5] but thinner than in the Nunes cohort (5.0 mm) [30].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We have also shown that the most common histological subtype in HFM is ALM, which stays in concordance with studies of other authors such as Durbec et al, Albreski et al,Jung et al,Nunes et al [2,9,28,30]. Many HFMs were ulcerated (62.4%), which is consistent with the retrospective literature in this MM group [2,30,33]. In the HFM group, we found a higher median Breslow thickness (3.3 mm) than reported by Bello (2.1 mm) [5] but thinner than in the Nunes cohort (5.0 mm) [30].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the median age in the non-HFM cohort was 52.5 years old, which is consistent with data in the literature [31]. There were slightly more women in the HFM (59.5%) and SUM groups (58.7%), which is consistent with the previous literature [11,30,32]. We have also shown that the most common histological subtype in HFM is ALM, which stays in concordance with studies of other authors such as Durbec et al, Albreski et al,Jung et al,Nunes et al [2,9,28,30].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations